A comparative analysis of forums and wikis as tools for online collaborative learning. (August 2017) - Biasutti, Michele
Abstract: The current paper presents a comparative analysis of forums and wikis as tools for online collaborative learning. The comparison was developed analyzing the data collected during a collaborative experience in an asynchronous e-learning environment. The activities lasted five weeks and consisted of forum discussions and designing a project in a wiki environment. The research method included both quantitative and qualitative analyses. A quantitative comparison of forums and wikis was developed applying the coding scheme based on the following indicators: (1) inferencing, (2) producing, (3) developing, (4) evaluating, (5) summarizing, (6) organizing, and (7) supporting. The qualitative aspects were assessed using an open-ended questionnaire for collecting participants' perspectives on the functionality of the collaborative tools. Results provided evidence of the different processes during the forum and wiki activities: processes such as inferencing, evaluating, organizing and supporting characterized forum discussions while wikis induced mainly processes of producing and developing. Different purposes were also evident: forums were useful for discussing, sharing ideas while wikis were used for developing a common collaborative document. In addition, the perceived time involved in performing the activities was different: forums were easier to access than wikis, while wikis required more time and were more difficult to use than forums. As a general conclusion it is not possible to state the superiority of one tool over another because each has its own characteristics and could be used with different purposes. Forums and wikis could have complementary functions and should be organized to complete each other for scaffolding students' self-regulated strategies and learning. The findings are discussed in the framework of designing collaborative virtual courses with proper tool selection. Highlights: Forums and wikis activities were compared for processes and functions. The knowledge construction processes were analyzed using content analysis. Forums activate mainly processes of inferencing, evaluating, organizing and supporting. Wikis induce mainly processes of producing and developing. Each tool has his own characteristics and functions and is complementary to the other.